Dysautonomia Is Linked to Striatal Dopamine Deficits and Regional Cerebral Perfusion in Early Parkinson Disease. (August 2020) - Shin, Hae-Won; Chung, Seok Jong; Lee, Sangwon; Cha, Jungho; Sohn, Young H.; Yun, Mijin; Lee, Phil Hyu
Abstract : Purpose: The aim of this study was to investigate the association between autonomic dysfunction and striatal dopamine depletion or metabolic changes in de novo Parkinson disease (PD). Methods: Based on the Composite Autonomic Severity Score (CASS), patients with de novo PD were classified into PD with (PD-AUT+) and without autonomic dysfunction (PD-AUT−) groups. We compared the dopamine transporter (DAT) availability in the striatum by quantitatively measuring 18 F-FP-CIT PET between both groups. We also assessed the association between DAT availability and the CASS. In addition, we compared regional uptake in early-phase images of 18 F-FP-CIT PET as well as cortical thickness between the PD-AUT+ and PD-AUT− groups. Results: The PD-AUT+ group had significantly lower DAT availability in all striatal subregions than did the PD-AUT− group. The total CASS was significantly correlated with DAT availability in all striatal subregions. In addition, the subscores of the adrenergic component were correlated with DAT availability in all striatal subregions. The subscores of the cardiovagal component were negatively correlated with DAT availability in the caudate and ventral striatum. In early-phase 18 F-FP-CIT PET, the PD-AUT+ group exhibited decreased regional perfusion in the parieto-occipital areas and increased regional perfusion in the pallidothalamic, pontocerebellar, inferior frontal, and primary motor areas compared with the PD-AUT− group. There were no regions of different cortical thickness between the PD groups. Conclusions: The present study revealed that autonomic dysfunction is closely linked to striatal dopamine depletion and prominent PD-related perfusion patterns in de novo PD, suggesting a greater pathological burden in patients with dysautonomia.